Resource Description and Access (RDA): the before and after the 3R Project - Soares Cavalheiro, Karen Cristina (2023)
The Resource Description and Access was developed by the Resource Description and Access Steering Committee as a set of data elements for creating metadata for library and cultural heritage resources. In 2017, the Library Reference Model conceptual model was published, consolidating a single structure as a reference model for libraries. There is an intensification of the use of Semantic Web technologies, such as Linked data, which presents a new perspective for describing and linking data. With these changes, the RDA Steering Committee group verified the need for a new Resource Description and Access structure, the 3R Project, which reformulated the structure of the Resource Description and Access Toolkit site aligned with Library Reference Model. The guiding question of this research was: what are the main changes in the Resource Description and Access with the 3R Project? The general objective of this research was to present the changes in the Resource Description and Access considering the changes developed in the 3R Project. The comparative method was used to analyze the structures of the two versions of the Resource Description and Access. As result, it was observed that the main changes in the Resource Description and Access Project 3R can be divided into three aspects: 1) changes in the site; 2) Structural changes in the guidelines and 3) changes related to the approximation with the scenario of publishing data on the Web and Linked data. It is concluded that the 3R project caused changes in the usability of the Resource Description and Access Toolkit, in the structure of the Resource Description and Access guidelines and promoted approximations with the Library Reference Model with Linked data. Efforts are needed to understand the most efficient means of applying the Resource Description and Access Project 3R guidelines in Cataloging and in the areas of Cataloging research and teaching.